Kepastian Hukum Jangka Waktu Hak Atas Tanah Bagi Pelaku Usaha di Ibu Kota Nusantara dalam Upaya Menciptakan Iklim Usaha yang Kondusif Bagi Penanaman Modal - Amelia Sundari Waliyani; Yani Pujiwati; Purnama Trisnamansyah (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
The development project of Nusantara Capital City in Indonesia (NCC) requires a cost of IDR 466 trillion with a financing scheme from the State Budget and the rest is obtained through the KPBU Scheme or private investors. In order to attract business actors to invest in NCC the government provides investment facilities by providing fiscal and non-fiscal incentives, one of which is the provision land rights for 2 (two) cycles for a period of 95 (Ninety Five) Years and 80 (Eighty) Years for cultivation rights, building use rights, and Rights to Use above management rights OIKN which are regulated in PP 12/2023 which has been amended by PP 29/2024. The purpose of the study was to determine the legal certainty of granting a land rights period in NCC reviewed with land regulations in Indonesia, namely based on Law Number 5 of 1960 concerning Basic Agrarian Principles and PP Number 18 of 2021 concerning Management Rights, Land Rights, Apartment Units and Land Registration in an effort to create a conducive business climate for investment. The research method used is normative juridical using descriptive analysis research specifications. The research stages used are library research and field research with data collection techniques by means of document studies by collecting data and reviewing secondary data related to the problem being studied, this library research was conducted to obtain primary legal materials, secondary legal materials and tertiary legal materials and interviews conducted with Legal Experts for the Deputy for Planning and Land Affairs of OIKN and one of the investors in the field of education who is currently in the process of establishing a university in Nusantara Capital City. This study found that the implementation of the Land Rights period based on PP 12/2023 which was amended by PP 29/2024 for business actors in Nusantara Capital City. does not provide legal certainty because the regulations are contrary to those stipulated by UUPA, PP 18/2021 and UUPM. A conducive business climate in the IKN has not been achieved optimally because one of the reasons is the failure to fulfill legal certainty regarding land rights in the Nusantara Capital City.. However, the provision of investment facilities in the PP apart from land Rights, is another consideration for business actors to invest and has shown an increase in investment interest influenced by other incentives provided by the government such as ease in business licensing, and reductions in various taxes such as income tax and 0% BPHTB.